2014
DOI: 10.1007/s10822-014-9748-9
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and experimental validation of novel potential chemopreventive agents using random forest and support vector machine binary classifiers

Abstract: Compared to the current knowledge on cancer chemotherapeutic agents, only limited information is available on the ability of organic compounds, such as drugs and/or natural products, to prevent or delay the onset of cancer. In order to evaluate chemical chemopreventive potentials and design novel chemopreventive agents with low to no toxicity, we developed predictive computational models for chemopreventive agents in this study. First, we curated a database containing over 400 organic compounds with known chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Instead of using all available descriptors, descriptor selection was integrated into the modeling procedure, e.g., the genetic algorithm (74,75) and simulated annealing (76). Instead of using linear regression, new machine learning approaches, which were developed based on nonlinear modeling algorithms such as k-nearest neighbors (77), support vector machines (78), and random forest (79,80), were used frequently in modeling studies from the 1990s to the 2000s. In the same period, model validation was emphasized and treated as a must-have component of modeling (81).…”
Section: Advancing Artificial Intelligence From Machine Learning To Deep Learningmentioning
confidence: 99%
“…Instead of using all available descriptors, descriptor selection was integrated into the modeling procedure, e.g., the genetic algorithm (74,75) and simulated annealing (76). Instead of using linear regression, new machine learning approaches, which were developed based on nonlinear modeling algorithms such as k-nearest neighbors (77), support vector machines (78), and random forest (79,80), were used frequently in modeling studies from the 1990s to the 2000s. In the same period, model validation was emphasized and treated as a must-have component of modeling (81).…”
Section: Advancing Artificial Intelligence From Machine Learning To Deep Learningmentioning
confidence: 99%
“…A consensus model can be created by leveraging the outputs of several individual QSAR models into one prediction. Previous work has demonstrated these models to have comparable or superior predictive capabilities compared to their individual components. In this work, a consensus model prediction was created by averaging the predicted classification of compound across all machine learning algorithms tested. Therefore, predictions by the consensus model were based on agreement of each algorithm’s predicted classification and ranged from 0 to 1.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Combi QSAR is a method for constructing models by combining molecular descriptors in multiple commercial software and multiple algorithms ( k -nearest neighbor, support vector machine, decision trees, and random forest). 25 28 It was reported that high prediction accuracy and stable results were obtained by using these methods. 25 28 Furthermore, Brownfield et al .…”
Section: Discussionmentioning
confidence: 99%
“… 25 28 It was reported that high prediction accuracy and stable results were obtained by using these methods. 25 28 Furthermore, Brownfield et al . proposed a prediction method that combined three class systems by a fusion process as a consensus classification.…”
Section: Discussionmentioning
confidence: 99%